'Discipled by praxis: soul and role in context'*. Issue 1 (1st January 2019) - Paterson, Michael
ABSTRACT: Aristotle held that humans had three basic activities each of which were directed towards a distinct goal or telos : theoria, thinking or analysing, directed towards the pursuit of truth; poiesis, making or bringing forth, directed towards crafting or producing and praxis, doing or applying a skill, directed towards action. In terms of theoria, this article critiques the pastoral cycle; enumerates five categories of reflection and outlines an approach to the reflection that fosters dialogue between soul, role and context. It goes on to craft and shape that thinking in story, image and autoethnographic writing with the aim of bringing forth the reader's own creative performance (poiesis) . It concludes by exploring the relevance of, and challenges to, reflective practice for practical theologians (praxis) .